Menopause and menopause. - Pacheco Romero, José (2015)
The author considers the impact menopause bas and will have on Peruvian women. The Peruvian physician and, mainly, the gynecologist needs adequate knowledge on the physiopathology of elderly women, early and late consequences, and available therapeutic measures and their effectivity. All women with climacteric syndrome and postmenopausal symptoms or with risk of either cardiovascular disease or osteoporosis are candidates for estrogen administration. Pretreatment evaluation includes clinical history and complete physical exam, breast and pelvic examination and hormone dependent cancer screening. Papanicolaou, basic laboratory work up, HDL and LDL cholesterol fractions and triglycerydes studies will be done routinely, as well as, mammography, pelvic ultrasound and bone densitometry in specific cases. When estrogens are to be employed, the lowest effective dose will be used. Progestins will be added either cyclically or continuosly if the woman has her uterus. Initial follow-up will be at two and six months, and then annually, to determine estrogen effectivity and absence of secondary effects and cancer. Though benefits of replacement hormone therapy are evident, life expectancy would increase less than one year. (Ginecol. Obstet. Perú 1994, 40: 6-25).